IbM KELOMPOK TANI SEJAHTERA YANG MENGHADAPI VIRUS KERITING PADA TANAMAN CABAI RAWIT(Capsicum frutescens L.) DI DESA KEDUNG PADANG, REJOSO, NGANJUK - Utami, Sri; Ardhi, Muh. Waskito; Prabowo, Sigit Ari (Jurnal Terapan Abdimas, 2016)
Thrips disease in pepper is a complicated issue that is perceived chili farmers in Kedung Padang. The disease is transmitted by Thrips pest sp resulting curly chili plants that do not produce fruit to the fullest. Scarcity and high price of chemical fertilizers made chili farmers find it difficult to get it. In addition, the negative impact of the use of chemical fertilizers to health neglected by farmers chili. The issues above pushed to perform the application of science and technology to society. Objectives and targets are IbM outcomes; (1) raise awareness of the dangers of the use of chemical insecticides; (2) counseling and manufacture of insecticides to control the mahogany seed Plant Pest Organisms (OPT) and; (3) reduce production costs; (4) increase the harvest of chili. The method used in IbM is using extension approaches and manufacture of insecticides from seed Mahogany and direct application on agricultural land area of ¼ acre pepper plants. IbM carried out for 12 months with activities and work procedures as follows; (1) manufacture of product samples; (2) extension hazards of chemical insecticides and manufacture of insecticides; (3) application of insecticides on ¼ acre of agricultural land cayenne pepper. IbM been carried out for 11 months ie from January to November 2014. The activities that have been carried out, among others; (1) manufacture of mahogany seed insecticide product samples; (2) insecticide application mahogany seeds ¼ acres of agricultural land cayenne pepper. Extension hazards of chemical insecticides and insecticide-making mahogany seeds. Keywords: Capsicum frutescens L, insecticides mahoni, prosperous farmer groups.